THERMAL, MECHANICAL, AND MICROSTRUCTURE CHARACTERISTICS OF PAEDERIA FOETIDA FIBERS/CARBON POWDER HYBRID REINFORCED EPOXY COMPOSITES - Sari, Nasmi Herlina; Suteja; Syafri, Edi (Association of Indonesian Forestry and Environment Researchers and Technicians, 2025)
Increased environmental and sustainability awareness has fueled efforts to develop bio-based composite materials for a wide range of end-use applications, as well as new alternatives to non-renewable synthetic fibers such as glass and carbon-reinforced composites. Considering development and research, Paederia foetida fiber stem (PFs) reinforced composites have recently generated a lot of interest. Hybrids of PFs with carbon powder (CP) have been explored in order to achieve the best properties for composites. This study focused on investigating the microstructural, mechanical, thermal, and density characteristics of hybrid reinforced epoxy composites made of CP/PFs. Several compositions of PFs and CP (30:0, 20:10, 15:15, 10:20, and 0:30 vol.), were prepared to manufacture composite using a hot press method. The effect of the volume fraction of carbon/PFs on the mechanical, thermal, and fracture structure properties of hybrid composites was examined. The findings showed that sample CDS20 which was made up of 20% PFs and 10% CP had the highest tensile strength (42.3 ± 2.7 MPa) and elastic modulus (2310.8 ± 91 MPa). It also had quite high thermal resistance properties with a residual charcoal content of about 23.8%. SEM analysis showed agglomeration of CP and the number of voids decreased as the volume fraction of PFs increased, and the interfaces between CP-PFs-epoxy appeared denser. For infrastructure applications, this composite may serve as an alternative to epoxy composites reinforced with sisal fiber.